Immediate Postoperative Improvement in Gait Parameters following Primary Total Knee Arthroplasty Can Be Measured with an Insole Sensor Device - Pfeufer, Daniel; Monteiro, Priscila; Gililland, Jeremy; Anderson, Mike B.; Böcker, Wolfgang; Stagg, Marissa; Kammerlander, Christian; Neuerburg, Carl; Pelt, Christopher (The Journal of Knee Surgery, 2020)
Total knee arthroplasty (TKA) improves the quality of life in those suffering from debilitating arthritis of the knee. However, little is known about the influence of TKA on restoring physical function. Prior studies have used artificial means, such as instrumented treadmills, to assess physical function after TKA. In this study an insole sensor device was used to quantify parameters of gait. The purpose of this study was to evaluate the ability of a wearable insole sensor device to measure immediate postoperative gait parameters at 2 weeks and 6 weeks following primary TKA and to determine if the device was suitable and sensitive enough to identify and measure potentially subtle changes in these measures at these early postoperative time periods. Twenty-nine patients with unilateral TKA, without contralateral knee pain, and aid-free walking before surgery were evaluated. An insole force sensor measured the postoperative parameters while walking a distance of 40 m on level ground at 2 and 6 weeks after TKA. The loading rate of the operated lower extremity was an average of 68.7% of the contralateral side at 2 weeks post-surgery and increased to 82.1% at 6 weeks post-surgery (p < 0.001). The mean gait speed increased from 0.75 to 1.02 m/s, (p < 0.001) and cadence increased from 82.9 to 99.9 steps/min (p < 0.001), while the numeric pain scale at rest decreased from 3.5/10 to 2.2/10, (p < 0.001) and the pain while walking from 3.9/10 to 2.4/10, (p < 0.001) from 2 to 6 weeks post-surgery. A significant improvement in gait parameters is detectable in the first 6 weeks after surgery with the use of a wearable insole device. As the gait speed and cadence increase and the VAS pain level decreases, the loading rate and average peak force begin to normalize. This device may allow for early gait analysis and have potential clinical utility in detecting early differences in patients' functional status following TKA.
Keywords: gait analysis; rehabilitation; total knee arthroplasty; physical function